1997
DOI: 10.1177/030098589703400105
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Malignant Melanomas in 57 Cats: Identification of (Amelanotic) Signet-ring and Balloon Cell Types and Verification of Their Origin by Immunohistochemistry, Electron Microscopy, and In Situ Hybridization

Abstract: Cutaneous malignant melanomas in cats, both melanotic and amelanotic, were diagnosed in 57 of 1.530 skin tumors during the period 1991-1995. All melanomas occurred in domestic shorthaircats of ages 3-19 years (mean = 11.5 years). Postmortem examination was performed on 16 cats. All had metastases in the regional lymph node and several organ systems. The average time of survival after surgical removal of the tumor was 4.5 months. Histologically, five types of melanomas could be distinguished: epithelioid, spind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 32 publications
2
56
0
4
Order By: Relevance
“…115 Primary balloon cell melanoma in brain arising from a melanoblastic meningeal (or diffuse meningeal) nevus has been described. 116 Amelanotic balloon cell melanoma represents a common histologic variant in the spectrum of feline malignant melanoma 117 and has also been described in humans. 118 This unusual neoplasm has been reported in the choroid.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…115 Primary balloon cell melanoma in brain arising from a melanoblastic meningeal (or diffuse meningeal) nevus has been described. 116 Amelanotic balloon cell melanoma represents a common histologic variant in the spectrum of feline malignant melanoma 117 and has also been described in humans. 118 This unusual neoplasm has been reported in the choroid.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Dutta et al [2] reported an amelanotic malignant melanoma on the cervical skin of a ground squirrel. Although considered to be absent in canine and feline melanomas [10,16], cytokeratin has been observed in human malignant melanomas [4]. Our report describes a case of malignant melanoma of the eyelid skin in a red squirrel, in which cytokeratin immunoreactivity was detected.…”
mentioning
confidence: 76%
“…Sci. 64(3): 261-264, 2002 Malignant melanoma of the eyelid has been reported in dogs [8], cats [16] and man [11]. Dutta et al [2] reported an amelanotic malignant melanoma on the cervical skin of a ground squirrel.…”
mentioning
confidence: 99%
“…12 Mixtures of signet-ring and epithelioid-type cells have been reported in dogs and cats. 8,25 Divergent differentiations as reported in human malignant melanomas such as fibroblastic or myofibroblastic, Schwannian and perineurial, smooth muscle, rhabdomyosarcomatous, osteocartilaginous, ganglionic and ganglioneuroblastic, neuroendocrine, and epithelial are not clearly distinguished as such in the WHO DA. 3,12 In our case, myofibroblastic differentiation as opposed to proliferation of reactive stromal myofibroblasts was supported by histologic features such as anisokaryosis and anisocytosis of these cells, the appearance of very plump spindle cells suggesting they may represent intermediate cells between signet-ring and spindle cells, and the overall irregularity in which spindle cells interweave between signet-ring cells that is not typical for stromal cells (Fig.…”
Section: Research-article2016mentioning
confidence: 99%
“…8,17,25 Electron microscopy revealed that the signet-ring cell morphology is caused by numerous aggregates of vimentin-positive intermediate filaments. 1,23,25 Comparable to previous canine and feline studies, the presented tumor was amelanotic, confirmed by negative Fontana staining, which made the diagnosis of melanoma even more difficult and strengthened the need for expression pattern analysis of the tumor cells. 8,25 All feline and canine signet-ring cell melanomas reported to date were positive for vimentin, S100, and NSE; however, melan A was not tested or only present in 1 canine case.…”
Section: Research-article2016mentioning
confidence: 99%